Profitability, Managerial Ownership, And Investment Opportunity Set On Dividend - Rino Tam Cahyadi; Tarsisius Renald Suganda (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
Dividend payment is one way to reduce agency costs between the company and shareholders. However, in facts that not all companies listed on the Indonesia Stock Exchange in 2016-2018 distribute dividends continuously. This study aims empirically to examine the effect of profitability, managerial ownership and investment opportunity sets on dividends. The population of this study are all listed companies on the Indonesia Stock Exchange which carry out corporate actions in the distribution of cash dividends at the Indonesian Central Securities Depository (KSEI). The research sample of 18 companies from various industries which carried out corporate actions at KSEI. This research is a quantitative study using the common effect panel data regression . The results showed that profitability had a positive effect on the dividend payout ratio and the investment opportunity set had a negative effect on the dividend payout ratio. This research contributes that the adequacy of internal funding affects the level of dividend distribution. In addition, companies that have high and stable profitability will tend to distribute dividends continuously. Conversely, if the company has many investment projects in the future, the dividend distribution will be smaller as long as the company is still focused on investment projects.